Low-carbon cement development: modifying volcanic ash reactivity for portland cement replacement - Nawaf Alsulami; Hung-Liang Roger Chen (Low-Carbon Materials and Green Construction)
Abstract Volcanic ash (VA) reactivity is typically low and requires activation or modification to expand its applicability. This study focuses on modifying the VA reactivity by introducing optimal mixing proportions of amorphous materials (AM) and by developing a reliable reactivity measurement technique based on the standard Ca(OH)2-reactivity test (CRT). CRT was used as a reference test to quantify the reactivity of four VAs. Optimal AM addition was used to increase the reaction rate and to take advantage of synergistic effects on the strength of mortars. Replacing VA with 15 wt.% silica fume (SF), 30 wt.% slag (SL), or 25 wt.% metakaolin (MK) to form modified-VA (MVA) significantly improved the strength and reactivity. The standard CRT was modified by utilizing a constant w/b ratio of 0.484 and by changing the curing regime where the ambient temperature was set to 43℃ for up to 91 days. This revised CRT is referred to as the “modified-Ca(OH)2-reactivity test” (MCRT). A relationship between the strength and the heat was used as a foundation to develop a classification that determines the level of reactivity of VA/MVA. The results indicate that three of the four VAs evaluated were found to be reactive. The synergistic actions within MVA mixtures significantly improved the reactivity at early ages. Results show that MVA mortar mix with 70% volcanic ash and 30% slag can achieve 25.6 MPa compressive strength at 91 days. By substituting 15% SF, 30% SL, or 25% MK for VA to form MVA, the mixes provide promising results for an alternative concrete mixture for future industrial applications.